Apakah Career Website Employer, Social Media and Employer Branding Mempengaruhi Daya Tarik dan Keinginan Melamar pada Industri Perbankan? (Do Employer Website Career, Social Media and Employer Branding Affect the Attractiveness and Desire to Apply in the Banking Industry?) - Dediek Tri Kurniawan; Adelia Shabrina Prameka (UPT Penerbitan Universitas Jember, 2022)
Along with the growth of internet users and active social media users in Indonesia, HR practitioners recommend using these media in the recruitment process. This study aims to examine how career website, employer branding, and social media in companies as employers affect organizational attractiveness and intention to apply in banking companies. The data analysis method used in this research is the Structural Equation Model (SEM) which is processed using LISREL software. The respondents of this study were students from the State University of Malang as many as 231 students. The findings of this study confirm the relationship of employer branding to the attractiveness of organizations in the banking industry. Social media also has a positive effect on the attractiveness of the organization and the desire of students to apply to the banking industry. The role of using a career website is important in increasing the attractiveness of the organization even though it does not create a desire to apply to the banking industry.